Effects of atrazine on the histology and expression of NOS and IP3 receptor in cardiac and cerebellar Purkinje cells of juvenile and adult Xenopus frog - Asouzu Johnson, Jaclyn Ezioma (My University, 2017)
Atrazine is a synthetic pesticide, which is extensively used in agriculture and horticulture to boost crop quality and meet food demands of the growing human population. Atrazine‟s physical properties enable it to be transferred from point of application to non-targeted areas, gain access to water sources and persist in environment following application. Atrazine has been shown to be embryotoxic but the effects reported in adult species have been mostly on endocrine disruption and gonadal morphology. It is hypothesized that atrazine might affect cardiac contractility and cerebellar synaptic transmission by disrupting the expression of homeostatic proteins. Ten- days old juvenile and 270 days old adult Xenopus frogs divided into 4 groups; one control group and three experimental groups were exposed to atrazine at concentrations of (0.01 μg/L, 200 μg/L and 500 μg/L) for 90 days. Harvested hearts and brains were processed and the morphological, histological investigations made (Mallory one step connective tissue stain for cardiac and cresyl violet stain for cerebellum). Additionally, immunohistochemical and immunofluorescence expression of key homeostatic calcium gated channel proteins; NOS and IP3R in cardiac and cerebellar tissues of the juvenile and adult frogs were measured. Mallory one step connective tissue stain revealed increased dilated cardiomyopathy effects such as thin wavy myocytes and infiltration of connective tissue in 0.01 μg/L and 200 μg/L treated frog groups, whereas hypertrophied cardiomyopathy effects; thickened darkly stained myofibrils were observed in sections of the heart from 500 μg/L groups in both juvenile and adult frogs. Immunohistochemistry and immunofluorescence cardiac eNOS expression was decreased in 200 μg/L and 500 μg/L treated frog groups in both juvenile and adult frog groups. The IP3R expression in adult frog‟s heart insignificantly (p > 0.05) increased and decreased in 0.01 μg/L and 500 μg/L groups respectively, and significantly decreased (p<0.03) in the 200 μg/L group. These changes are suggestive features of cardiac arrhythmias. Immunohistochemistry and histology (Cresyl violet stain) of the cerebellar cortex (in juvenile and adult frog groups) reveal reduction in the number of Purkinje cell expressing IP3Rs relative to atrazine doses/concentrations, suggesting visual and/or motor function effect. In addition IP3Rs expressions were significantly decreased (p < 0.037) in all the treated juvenile groups, indicating greater cerebellar toxicity of atrazine on juvenile Xenopus species. In conclusion atrazine exposure (low dose to high doses) showed some alterations on Purkinje cells immunochemical expression in the heart and cerebellum and these effects were more severe in the juvenile than the adult frog. In addition, the high juvenile mortality and distinct histological alterations characteristic of cardiomyopathy, arrhythmia and disruptive motor effects reported in both juvenile and adult groups indicate the potential toxicity of atrazine at high concentrations in marine habitats and the ecosystem at large.
A dissertation submitted to School of Anatomical Sciences Faculty of Health Sciences University of the Witwatersrand, in fulfilment of the requirement for the degree of Master of Science in Medicine. Johannesburg 2017.
Keywords: Cerebellar Purkinje; Atrazine